2011
DOI: 10.1111/j.1369-1600.2010.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime cigarette smoking is associated with striatal volume measures

Abstract: Nicotine, the primary addictive component of tobacco, affects the mammalian brain. Smokers' brains have smaller cortical grey matter volumes and/or lower densities compared with non-smokers'. Differences in subcortical structures like the striatum are however, less clear. A high concentration of nicotinic receptors makes the striatum a potential target for nicotine. In addition, striatal nuclei are essential components of the reward/reinforcement pathway involved in addiction. The aim of this study was to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
62
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 36 publications
7
62
2
Order By: Relevance
“…In addition, our novel surface area and shape findings provide more nuanced insight into the relationship between striatal morphology and craving. The relationship between craving and left lateralized striatal volume and surface area is consistent with previous findings linking stimulant abuse with greater left striatal volume (Das et al, 2011;Churchwell et al, 2012, Ersche et al, 2012. The connection between the left striatum and substance abuse may be tied to the more dominant role of the left hemisphere in reward and approach behavior (Davidson and Irwin, 1999).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In addition, our novel surface area and shape findings provide more nuanced insight into the relationship between striatal morphology and craving. The relationship between craving and left lateralized striatal volume and surface area is consistent with previous findings linking stimulant abuse with greater left striatal volume (Das et al, 2011;Churchwell et al, 2012, Ersche et al, 2012. The connection between the left striatum and substance abuse may be tied to the more dominant role of the left hemisphere in reward and approach behavior (Davidson and Irwin, 1999).…”
Section: Discussionsupporting
confidence: 78%
“…For example, enhanced striatal surface area has been associated with obsessive-compulsive disorder (OCD; Shaw et al, 2014), suggesting that larger striatal surface area may be a feature of compulsive disorders including OCD and addiction. Finally, our research focused only on the relationship between striatal morphology and cigarette craving as previous research has shown a clear link between stimulant abuse and enhanced striatal volume when substance abusers and healthy controls were compared (Das et al, 2011;Churchwell et al, 2012, Ersche et al, 2012. It is unclear whether variability in striatal morphology, in non-abusing populations also may explain individual differences in craving severity for other, more natural, reinforcers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nicotinic acetylcholine receptor (nAChR)s are extensively distributed in the human brain, with the highest density in the thalamus, substantia nigra and cerebral cortex in a decreasing order as well as cerebral vasculature and astrocytes [9,[20][21][22]. Given the associations of brain region and subtype specific attenuations in nAChRs with neuropsychiatric diseases including Alzheimer's and Parkinson's diseases, dementia with Lewy bodies, schizophrenia and autism, studies revealing improvement following nicotine treatment in the animal Parkinsonian models, and larger putamen volumes in individuals with a greater lifetime nicotine exposure, nicotine has been regarded to have a neuroprotective effect [22][23][24]. Either through mesolimbic system activation by nicotine addiction or binding to mostly concentrated nAChRs in the striatum, volume changes in striatum with subsite-dependent alterations have been reported.…”
Section: Discussionmentioning
confidence: 99%